Responsibility for core international crimes: connecting the dots toward a duty to end impunity - Botte, Auriane (2017)
This thesis begins with the observation that a gap exists between the universal consensus among all States regarding the criminalisation of genocide, crimes against humanity and war crimes on the one hand, and the prevalence of impunity on the other. It then puts forward the hypothesis that this gap may be explained by the unsuitability of the approach taken by the international community to address the issue of responsibility for core international crimes. In order to test this hypothesis, this thesis critically examines the different forms of responsibility for core international crimes available in International Law. One of the important characteristics that distinguish core international crimes from other international crimes or ordinary crimes is that they are often committed with the simultaneous participation of several actors, including individual perpetrators, the State and, in some instances, non-state actors. Addressing the impunity for the commission of core international crimes cannot, therefore, be limited to the lack of consequences for individual perpetrators. This thesis challenges the focus of International Criminal Justice on individual criminal responsibility and argues for a comprehensive approach to responsibility for international crimes, including State and collective responsibility, in order to convey the collective and political features of these crimes. The issue of responsibility for genocide, crimes against humanity and war crimes has been widely discussed in the scholarly literature, in particular with the development of International Criminal Law. One can observe, however, an imbalance between the amount of research dedicated to the issue of individual criminal responsibility for core international crimes and the issue of State responsibility for international crimes. This imbalance is partly due to the fact that the notion of State criminal responsibility was rejected by a large majority of States, and discussions on these issues were abandoned. The originality of this thesis comes from the broad approach it adopts to examine the issue of responsibility for core international crimes with the aim of bridging the gap between the distinct academic perspectives. It weaves together different approaches to responsibility, from individual responsibility to State responsibility, in order to identify the weaknesses of the current forms of responsibility and to highlight the complementary aspects of the main questions discussed in these different fields of law.